Dietary management for healthier batter formulations. (July 2021) - Ching, Liew Wen; Zulkipli, Nur 'Afifah Mat; Muhamad, Ida Idayu; Marsin, Aishah Mohd; Khair, Zulkifli; Anis, Siti Nor Syairah
Abstract: Background: A more frequent consumption of deep-fat fried food is believed to be linked with a higher risk of subsequently developing obesity and higher severe diseases. However, the evidence from long-term randomized trials or prospective epidemiological studies is scarce. Dietary management for a healthier consumption of food with low fat intake gives high contributions to health. Scope and approach: Despite the changes in lifestyle that acquire more favourable type of deep-fat fried food as the main dish, a dietary fibre-formulated batter could be the most suitable substitute without changing the taste to keep the health benefits within. Dietary fibre-formulated batter consists the same benefits as resistant starch that can reduce the blood cholesterol level, the glycaemic index and influence in digestive tract. In this review paper, we discuss the factors, properties, background and applications of fibres in batter formulations for oil uptake reduction. Key findings and conclusions: With high potential of health benefits, different types of dietary fibre have been explored as batter formulations. Dietary fibres are proven to reduce the oil uptake of fried food products as well as improving the textural and overall acceptability. The application of dietary fibre as batter rich in nutrients could be product-friendly for deep-fat fried food products. Highlights: Consumption of deep-fat fried food leads to higher risk of severe diseases. Raw materials selection and processing methods are the crucial factors of oil uptake. Oil uptake can be monitored by fibre addition, frying temperature and frying time. Fibre acts as barrier to reduce oil uptake and retain internal moisture content. Fibre-formulated batter improves textural and overall acceptability of fried food.